2002
DOI: 10.1161/01.cir.0000033115.92612.f4
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomic Mapping and Catheter Ablation of Breakthroughs From the Right Atrium to the Superior Vena Cava in Patients With Atrial Fibrillation

Abstract: Background-The superior vena cava (SVC) is one of the sources of ectopies that can initiate atrial fibrillation (AF). We investigated by radiofrequency ablation the electrophysiological characteristics of the junction of the right atrium (RA) and the SVC and the feasibility of electrical disconnection of the SVC from the RA. Methods and Results-Sixteen patients with paroxysmal AF after pulmonary vein isolation underwent electroanatomic mapping at the RA-SVC junction during sinus rhythm. Mapping showed sharp po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 14 publications
2
93
0
1
Order By: Relevance
“…7 Goya et al reported breakthroughs between the SVC and RA in 16 patients. 25 They were located in the anterior aspect of the RA-SVC junction in 3, laterally in 4, posteriorly in 10, and septally in 6 patients. In the present study the most likely location of SVC reconnection was the anterolateral SVC-RA junction.…”
Section: Svc-ra Electrical Connectionmentioning
confidence: 93%
“…7 Goya et al reported breakthroughs between the SVC and RA in 16 patients. 25 They were located in the anterior aspect of the RA-SVC junction in 3, laterally in 4, posteriorly in 10, and septally in 6 patients. In the present study the most likely location of SVC reconnection was the anterolateral SVC-RA junction.…”
Section: Svc-ra Electrical Connectionmentioning
confidence: 93%
“…The SVC is a structure second only to the PV in importance for treating AF. 8, [20][21][22][23][24][25][26] xternal cardioversion (EC) is sometimes used for terminating drug-refractory atrial fibrillation (AF) and is recognized as a useful treatment option for it. 1,2 Internal cardioversion (IC) is an alternative treatment that can be more effective and which delivers lower joule energy than EC.…”
mentioning
confidence: 99%
“…The revealed features seemingly contradict the common pathogenesis mechanisms according to which the AF occurrence is mainly due to the appearance of abnormal impulses in LA remodeling from the mouths of the pulmonary veins and throughout the tissue. Nevertheless, the superior vena cava is one of the sources of ectopies that can initiate AF, which was determined in a study performed by M.Goya et al [23]. Gaynor SL et al [24] showed that in dogs with chronic RV pressure overload, RV systolic function was preserved, but diastolic function was impaired.…”
Section: Fig 1 Causes Of Death In Dcm Patientsmentioning
confidence: 99%